Pairing-Based Cryptography - Pairing 2010 4th International Conference, Yamanaka Hot Spring, Japan, December 2010. Proceedings - Joye, Marc.; Miyaji, Atsuko.; Otsuka, Akira. (Lecture Notes in Computer Science,, 2010)
This book constitutes the refereed proceedings of the 4th International Conference on Pairing-Based Cryptography, Pairing 2010, held in Yamanaka Hot Spring, Japan, in December 2010. The 25 full papers presented were carefully reviewed and selected from 64 submissions. The contributions are organized in topical sections on: efficient software implementation; digital signatures; cryptographic protocols; key agreement; applications - code generation, time-released encryption, and cloud computing; point encoding and pairing-friendly curves; ID-based encryption schemes; and efficient hardware, FPGAs, and algorithms.